Specialty Corn for Enhancing Farm Profitability in peri-urban Agriculture - Karjagi, Chikkappa G.; Bhat, Jayant S.; Dass, Sain (Indian Farming, 2015)
Indian farmers, especially in the peri-urban areas can increase theirfarm profitability by growing specialty corns. Sweet corn and babycorn are recommended for peri-urban agriculture because of their shelf-life. The increasing popularity and demand for these specialty corns has atracted farmers to grow these types of corns in addition to the normal corns.